Investigating Iranian Midwifery Students' General and Professional Communication Skills and Their Viewpoints on the Ways of its Improvement using Data Triangulation - Sara Abedian; mozhgan javadnoori; Mahmood Maniati (Mashhad University of Medical Sciences, 2022)
Background & aim: Midwives need to have knowledge and skills of human communication to provide their professional services in the most efficient way. The purpose of this study was to investigate the general and professional communication skills of Iranian midwifery students and to explore their viewpoints on the ways of its improvement.Methods: This cross-sectional study using a data triangulation approach was conducted on 343 midwifery students who were selected using convenience sampling from Ahvaz Jundishapur University of Medical Sciences and Semnan Azad University, Iran, in 2020. Data were collected using Queendom Communication Skills Test-Revised (CSTR) and Professional Communication Skills Assessment Questionnaire. There was an open-ended question at the end of the questionnaire that assessed students' views on improving communication skills. The quantitative data were analyzed by SPSS version 22, and qualitative data by qualitative content analysis. Results: The mean scores of the students' general and professional communication skills were 64 ± 4.3 (poor) and 92 ± 3.1(moderate), respectively. No significant relationship was found between demographic or academic characteristics of midwifery students and their general and professional communication skills. Analysis of students' experiences and perceptions resulted in two main categories indicating the need to promote direct training and to control the impact of hidden curriculum.Conclusion: Most students had poor general communication skills while their professional communication skills were at a moderate level. Communication skills training in the midwifery curriculum needs to be revised. Results reflected the need to empower instructors and students in terms of their communication skills.